Ethical Policymaking in Higher Education: State Regulation of Religious Colleges in Maryland - Bennett, L. Leslie (A journal of church and state, 1993)
L. Leslie Bennett, Jr., David E. Sumler; Ethical Policymaking in Higher Education: State Regulation of Religious Colleges in Maryland, Journal of Church and Sta